The importance of conserved amino acids in heme-based globin-coupled diguanylate cyclases. - Xuehua Wan; Jennifer A Saito; James S Newhouse; Shaobin Hou; Maqsudul Alam (PLoS ONE)
Globin-coupled diguanylate cyclases contain globin, middle, and diguanylate cyclase domains that sense O2 to synthesize c-di-GMP and regulate bacterial motility, biofilm formation, and virulence. However, relatively few studies have extensively examined the roles of individual residues and domains of globin-coupled diguanylate cyclases, which can shed light on their signaling mechanisms and provide drug targets. Here, we report the critical residues of two globin-coupled diguanylate cyclases, EcGReg from Escherichia coli and BpeGReg from Bordetella pertussis, and show that their diguanylate cyclase activity requires an intact globin domain. In the distal heme pocket of the globin domain, residues Phe42, Tyr43, Ala68 (EcGReg)/Ser68 (BpeGReg), and Met69 are required to maintain full diguanylate cyclase activity. The highly conserved amino acids His223/His225 and Lys224/Lys226 in the middle domain of EcGReg/BpeGReg are essential to diguanylate cyclase activity. We also identified sixteen important residues (Leu300, Arg306, Asp333, Phe337, Lys338, Asn341, Asp342, Asp350, Leu353, Asp368, Arg372, Gly374, Gly375, Asp376, Glu377, and Phe378) in the active site and inhibitory site of the diguanylate cyclase domain of EcGReg. Moreover, BpeGReg266 (residues 1-266) and BpeGReg296 (residues 1-296), which only contain the globin and middle domains, can inhibit bacterial motility. Our findings suggest that the distal residues of the globin domain affect diguanylate cyclase activity and that BpeGReg may interact with other c-di-GMP-metabolizing proteins to form mixed signaling teams.